Asymmetric effects of luminance and chrominance in the watercolor illusion - Coia, Andrew J.; Crognale, Michael A. (Frontiers in Human Neuroscience, 2014)
When bounded by a line of sufficient contrast, the desaturated hue of a colored line will spread over an enclosed area, an effect known as the watercolor illusion. The contrast of the two lines can be in luminance, chromaticity, or a combination of both. The effect is most salient when the enclosing line has greater contrast with the background than the line that induces the spreading color. In most prior experiments with watercolor spreading, the luminance of both lines has been lower than the background. An achromatic version of the illusion exists where a dark line will spread while being bounded by either a darker or brighter line. In a previous study we measured the strength of the watercolor effect in which the colored inducing line was isoluminant to the background, and found an illusion for both brighter and darker achromatic outer contours. We also found the strength of spreading is stronger for bluish (+S cone input) colors compared to yellowish (-S cone input) ones, when bounded by a dark line. The current study set out to measure the hue dependence of the watercolor illusion when inducing colors are flanked with brighter (increment) as opposed to darker outer lines. The asymmetry in the watercolor effect with S cone input was enhanced when the inducing contrast was an increment rather than a decrement. Further experiments explored the relationship between the perceived contrast of these chromatic lines when paired with luminance increments and decrements and revealed that the perceived contrast of luminance increments and decrements is dependent on which isoluminant color they are paired with. In addition to known hue asymmetries in the watercolor illusion there are asymmetries between luminance increments and decrements that are also hue dependent. These latter asymmetries may be related to the perceived contrast of the hue/luminance parings.